Effect of 10% carbamide peroxide bleaching gels on surface hardness of nano filled composite resin - Mona, Deli; Rismayansari, Indah (Universitas Padjadjaran, 2019)
Introduction: Home bleaching is the whitening treatment of vital teeth applied by patients themselves at home under dentist supervision. In clinical condition, several patients who need bleaching treatment already had nano filled composite resin restoration on their teeth. The purpose of this study was to investigate the contact time difference of 10% carbamide peroxide bleaching gels application for home bleaching on the surface hardness of nano filled composite resin activated by Light Emitting Diode (LED). Methods: Total sample in this study was 30 samples, divided into 3 groups. The samples used were nano filled composite resin cylindrical shape with a diameter of 6 mm and a thickness of 2 mm. Group I as the control group was immersed in distilled water, group II was treated with immersion in 10% carbamide peroxide for 4 hours per day, and group III was immersed in 10% carbamide peroxide for 6 hours per day. The duration of treatment was 14 days for all groups. Data were analysed using Kruskal-Wallis with Mann-Whitney test and the p-value = 0.05. Results: The result of one-way Kruskal-Wallis with Mann-Whitney test showed that there were significant difference between the control group and the groups applied with 10% carbamide peroxide for 4 hours and 6 hours per day with the p-value 0.00 (p < 0.05). Conclusion: Application of 10% carbamide peroxide decreasing the surface hardness of nano filled composite resins activated by LED.Keywords: Nano filled composite resin, carbamide peroxide, composite resin hardness, Light Emitting diode (LED).